Perubahan Lapisan F Ionosfer di Atas Pontianak pada Saat Gerhana Matahari Cincin 26 Desember 2019 - Agri Faturahman; Jiyo Harjo Suwito; Faruk Afero; Adi Purwono (Jurnal Sains Dirgantara, 2022)
The Annular Solar Eclipse (ASE) occurred on December 26, 2019, across parts of Indonesia, including Pontianak. In connection with this event, we investigated the changes in the critical frequency of the F1 (foF1) layer, F2 (foF2) layer, and in the height of the peak density of the F2 (hmF2) ionosphere layer above Pontianak (0.03°S, 109.33°E, inclination -15.97°LS). Observations are every 5 minutes made using CADI ionosonde from a few days before until after the ASE. The result of the ionogram is then manually interpreted (scaling). The research results show: (1) response to eclipse by F2 layer is slower than F1 layer; (2) in the ASE period, the foF1 value drops to 1.55 MHz with an average NmF1 decrease rate of about 29 electrons/ /sec, then increases in the recovery phase with an average increase rate of about 15 electrons/ /sec, indicating asymmetry of the process of decreasing and increasing electron density in the F1 layer; (3) During the decreasing phase, foF2 decreases by 19% with an average NmF2 decrease rate of ~21 electrons/ /s, then NmF2 increases in the recovery phase at an average rate of ~20 electrons/ /s; (4) There was an increase in the peak F2 electron density a few minutes after the peak of eclipses with an average upward movement rate of about 27.8 m/s. It is due to a reduction in electron density and an upward drift caused by the polarization of the electric field in the eclipsed region. These results confirm the previous study on the effect of solar eclipses at low latitude ionospheric layers.